The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4315/0362-028x.jfp-11-007
|View full text |Cite
|
Sign up to set email alerts
|

Designing a National Restaurant Inspection Disclosure System for New Zealand

Abstract: The World Health Organization estimates that up to 30% of individuals in developed countries become ill from food or water each year, with up to 70% of these illnesses estimated to be linked to foodservice. Restaurant inspections aim to prevent restaurant-associated foodborne outbreaks while enhancing consumer confidence in the safety of food prepared in these establishments. Inspection disclosure systems have been developed as a tool for consumers and incentive for foodservice operators. Disclsosure systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Although the preferred format for disclosure at restaurants was a letter grade and numerical score, this appeared to be only a moderate preference over the other responses, and there was variation by how often a respondent ate out on average. In a study to inform a disclosure policy for New Zealand that compared a letter grade placard and speedometer-type gauge, the letter grade was preferred and was perceived to convey the information in a more interesting manner (8). Interestingly, our study found that respondents who currently work in food service preferred just a letter grade over the other options, which was also consistent with food service workers in New Zealand who preferred the letter grade over the speedometer gauge (8).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the preferred format for disclosure at restaurants was a letter grade and numerical score, this appeared to be only a moderate preference over the other responses, and there was variation by how often a respondent ate out on average. In a study to inform a disclosure policy for New Zealand that compared a letter grade placard and speedometer-type gauge, the letter grade was preferred and was perceived to convey the information in a more interesting manner (8). Interestingly, our study found that respondents who currently work in food service preferred just a letter grade over the other options, which was also consistent with food service workers in New Zealand who preferred the letter grade over the speedometer gauge (8).…”
Section: Discussionsupporting
confidence: 77%
“…In a study to inform a disclosure policy for New Zealand that compared a letter grade placard and speedometer-type gauge, the letter grade was preferred and was perceived to convey the information in a more interesting manner (8). Interestingly, our study found that respondents who currently work in food service preferred just a letter grade over the other options, which was also consistent with food service workers in New Zealand who preferred the letter grade over the speedometer gauge (8). Respondents who ate out on average one to two times or three to four times per week were the majority of those sampled and appeared to have similar responses.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance to this dissertation is policy development, implementation, and enforcement by the street-level bureaucrat; law-making is the purview of bureaucrats and adjudication is primarily used for dispute resolution (Howlett et al, 2009;Lobel, 2005;Skok, 1995). An example of a public policy solution to a food safety issue is the Toronto Public Health Dinesafe program, a 'name and shame' disclosure system in which restaurants are required to prominently display a colour coded placard indicating the results of its most recent public health inspection; this placard clearly and easily conveys the hygiene status of the food producer to the consumer (Filion & Powell, 2011;Medical Officer of Health, 2009; S. Thompson et al, 2005;Toronto Public Health, 2012a). This legislation recognizes a public health problem (foodborne illnesses resulting from food produced by a facility that does not meet the legislative standard) and the development, implementation, and execution of a public policy solution (the Dinesafe placard) in an attempt to achieve a goal (improved public health through a reduction in foodborne illnesses).…”
Section: Institutions: Public Institutions and Public Administrationmentioning
confidence: 99%
“…Food businesses must be licensed with one of the state's food safety institutions to produce, sell, or import food into Therefore, both businesses and the general public recognize that a license to operate a food business in Canada requires the government's institutions and actors to use the process of inspections to ensure safe food handling practices at that facility (Albersmeier et al, 2009;Law, 2003;Medeiros & Wilcock, 2006;Papadopoulos et al, 2012;Rouvière & Caswell, 2012). Trust in this system is further enhanced by the transparency of the government processes through such programs as Toronto Public Health's DineSafe program and the CFIA's list of Suspensions and Cancellations; these activities reduce information asymmetry by notifying the consumer or customer that the facility has not met its regulatory requirements for food safety activities (CFIA, 2017h; City of Toronto, 2012; Devaney, 2016;Filion & Powell, 2011;Papadopoulos et al, 2012;Thompson et al, 2005).…”
Section: Information Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation